PENGARUH KOMPETENSI DAN MOTIVASI KERJA TERHADAP KUALITAS LAYANAN PADA KPKNL PALU - PEBRIYANTI, DIAH (Fakultas Ekonomi Universitas Tadulako, 2017)
The purpose of this study are: 1) to determine the influence of competence and work motivation on service quality at KPKNL Palu; 2) to determine the influence of competence on service quality at KPKNL Palu; 3) to determine the influence of work motivation on service quality at KPKNL Palu. Sample consists of 72 people/employees representing their work units. Research method using multiple linear analysis method. The results indicate that Y = 0.068 + 0.152X1 + 0.839X2. The test shows that competence and work motivation simultaneously have significant influence on service quality. Partial tests show that competence has non-significant influence on service quality while work motivation significantly influence the quality of service. The determinant coefficient shows the value of R-Square of 0.904, which means that 90.4% of service quality are influenced by competence and work motivation, while the rest of 9.6% is influenced by other variables that are not examined in this study.